A framework for incorporating physical activity in treatment: Competencies, guidelines, and implications for family therapists. (4th September 2021) - Novak, Josh R.; Ellis, Faith K.
Abstract: Physical activity can have a profound impact on the cognitive, emotional, and social aspects of our clients' lives, and can even boost and sustain therapy outcomes. And yet, family therapists may not be trained or educated in the importance of physical activity nor how to assess, educate, and collaborate with health professionals to incorporate physical activity in treatment. As the evidence grows on the connection between physical activity and biopsychosocial functioning and more family therapists enter medical and healthcare settings, a framework for physical activity competencies is needed. As such, the purpose of this conceptual and empirical review paper is to (a) review the important brain‐boosting benefits of physical activity for mental, cognitive, and social health, (b) provide a framework for the domains for family therapists for incorporating exercise in assessment and treatment, and finally, (c) outline recommendations for practice, education and supervision, and research for family therapists.